Evaluating the Effectiveness of Sports Sponsorship from Banking and Financial Services, Case Study: Badminton - Pandandini, Afifah Khoirunnisah (Integrasi Sains Media, 2023)
Indonesia is known for its badminton success, yet its badminton and sports industry still has fundamental problems in its management, funding, and regulations impacting the athletes' performances. Whereas an athlete's performance is vital for the sponsors as it results in more exposure an athlete can expect to earn for the sponsors' visibility. Therefore, BNI's decision to sponsor the Indonesian badminton team is now arguable whether the company will benefit from this sponsorship deal. Previous research imposed the role of customer perceptions as the determinant of the sponsorship responses that implies the sports sponsorship effectiveness. Thus, the current research is meant to extend the understanding of sports sponsorship effectiveness, specifically from banking and financial institutions in the context of the Indonesian badminton team. The quantitative method through a questionnaire survey was chosen to conduct this research with a purposive sampling technique targeting the non-BNI users who are also the spectators of Indonesian international badminton tournaments in the last 2 years. The descriptive statistics and PLS-SEM were then utilized to analyze the 308 survey responses acquired. The results showed that consumers consider badminton events significant in Indonesia, although not for them. The sponsorship from BNI is also perceived as favorable and matches with the Indonesian badminton team. However, only some variables contribute positively to the sponsorship responses in brand awareness, corporate image, and purchase intention. To gain benefits from sports sponsorship, a company should attract the right target audience while showing real sincerity in sponsoring the sports property. Further research may be extended into other sports and locations of research to explain better the sports sponsorship effectiveness from consumers' perceptions.